2001
DOI: 10.1136/thx.56.9.696
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced survival of lung granulocytes in an animal model of asthma: evidence for a role of GM-CSF activated STAT5 signalling pathway

Abstract: BACKGROUNDAs granulocyte/macrophage colony stimulating factor (GM-CSF) mediated delay of granulocyte apoptosis contributes to the accumulation of inflammatory cells at the site of inflammation in many diseases, we sought to determine whether asthma is also associated with a GM-CSF dependent increase in lung granulocyte survival. Moreover, because GM-CSF mediates its effects through activation of signal transducer and activator of transcription 5 (STAT5), we also investigated the potential role of STAT5 in alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…30,31 In horses with RAO, indirect evidence suggests that GM-CSF enhances the survival of airway neutrophils. In 1 study, 32 investigators found that granulocytes isolated from the airways of affected horses had delayed apoptosis in vitro, compared with results for neutrophils isolated from control horses, and that this delay was suppressed by the addition of anti-GM-CSF antibodies. However, if GM-CSF is an important inflammatory mediator in horses with RAO, the source of it remains uncertain because analysis of data from another study 4 conducted by our laboratory group indicates that gene expression of GM-CSF in epithelial cells or BALF cells 4 is not upregulated during RAO.…”
Section: Discussionmentioning
confidence: 98%
“…30,31 In horses with RAO, indirect evidence suggests that GM-CSF enhances the survival of airway neutrophils. In 1 study, 32 investigators found that granulocytes isolated from the airways of affected horses had delayed apoptosis in vitro, compared with results for neutrophils isolated from control horses, and that this delay was suppressed by the addition of anti-GM-CSF antibodies. However, if GM-CSF is an important inflammatory mediator in horses with RAO, the source of it remains uncertain because analysis of data from another study 4 conducted by our laboratory group indicates that gene expression of GM-CSF in epithelial cells or BALF cells 4 is not upregulated during RAO.…”
Section: Discussionmentioning
confidence: 98%
“…Horses. The "heavy breathing" syndrome is considered to be a naturally occurring disease of horses, similar to human BA [ 50]. Within this syndrome, acute bronchial obstruction, bronchial hyper-responsiveness and chronic airway inflammation develop.…”
Section: Figure 1 -Steps For Inducing Animal Model Of Asthmamentioning
confidence: 99%